PENDISTRIBUSIAN DAN PENJERNIHAN AIR DI DESAGIRIHARJO KECAMATAN PANGGANG KABUPATEN GUNUNG KIDUL - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Giriharjo Village at panggang District, Gunungkidul Regency was a village that had clean water supply problem. Its villagers, having a monthly income in average of Rp 400.000,00, must spend around Rp 150.000,00 for clean water or otherwise they must walk to get water from Kaligede River 2 -4 km away from their home. Inorder to alleviate this problem, two separate team as parts of student community service program (KKN-PPM) UGM have been deployed on July-August 2008 and July-August 2009. As the result, a system of clean water supply using Solar Water Pumping System (SWPS) has been installed since the end of August 2009. However, there is no reliable distribution and purification system to provide equal access of clean water for the entire village. On the other hand, the system's frequent shutdowns caused by technical problems also became the main concern for the future program. The third student team was deployed on July-August 2010 to perform the remaining tasks. This team has successfully established a reliable distribution system. However, the water purification system has not been installed yet. There was a delay on the development of the water filtration prototype. The SWPS technical problems have been solved with the assistance of PAMMASKARTA, a Non Governmental Organization on water supply system for rural areas in Yogyakarta.